2019
DOI: 10.1007/s10942-019-00319-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Group IRT Measurement Invariance Analysis of the Forms of Self-Criticising/Attacking and Self-Reassuring Scale in Thirteen International Samples

Abstract: The purpose of this study was to examine the measurement invariance of the Forms of Self-Criticising/Attacking & Self-Reassuring Scale (FSCRS) in terms of Item Response Theory differential test functioning in thirteen distinct samples (N = 7714) from twelve different countries. We assessed differential test functioning for the three FSCRS subscales, Inadequate-Self, Hated-Self and Reassured-Self separately. 32 of the 78 pairwise comparisons between samples for Inadequate-Self, 42 of the 78 pairwise comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…Consequently, the most self-critical people (class 6 and 7 combined is 18.9%) are less common in the general population than the least self-critical people (class 1 and 2 combined is 33.7%). Similar to the findings of Halamová et al (2019), participants from Japan are the most self-critical, followed by Taiwan, while the least self-critical participants are from Israel and Portugal. In addition to their findings, in this article, we found that there are 5 classes of countries according to their level of self-criticism and 7 classes of participants according to their level of self-criticism.…”
Section: Discussionsupporting
confidence: 74%
“…Consequently, the most self-critical people (class 6 and 7 combined is 18.9%) are less common in the general population than the least self-critical people (class 1 and 2 combined is 33.7%). Similar to the findings of Halamová et al (2019), participants from Japan are the most self-critical, followed by Taiwan, while the least self-critical participants are from Israel and Portugal. In addition to their findings, in this article, we found that there are 5 classes of countries according to their level of self-criticism and 7 classes of participants according to their level of self-criticism.…”
Section: Discussionsupporting
confidence: 74%
“…In a large intercultural study from 12 different countries, Halamova et al (, ) reported that a bifactor structure appeared to better fit the data, although the original three‐factor solution had an acceptable fit. This research provides evidence that the two self‐critical scales, IS and HS, might not be considered different factors.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In a large intercultural study, Halamova, Kanovsky, and Pacuchova (); Halamova et al () referred to the translation of the FSCRS into 10 languages other than French, namely, Chinese (Yu, ), German (Krieger, Martig, van den Brink, & Berger, ), Hebrew (Shahar et al, ), Italian (Petrocchi & Couyoumdjian, ), Japanese (Kenichi, personal communication), Portuguese (Castilho, Pinto‐Gouveia, & Duarte, ), Slovak (Halamova et al, ), Swedish (Lekberg & Wester, ), Urdu (Yasien, Zia, & Yasmin, ), and Dutch (Sommers‐Spijkerman et al, ). A short form of the Dutch version has been validated.…”
Section: Introductionmentioning
confidence: 99%
“…Next, an item showing non-critical attitude ("I am accepting, non-critical and non-judgemental of my feelings of distress") was removed on compassion for self. Previous research shows that self-criticism is higher in Japanese individuals than individuals in other twelve countries [42]. Earlier research has also pointed out that self-criticism in Japanese individuals serve different functions than those in American, which might be caused by cultural differences [43].…”
Section: Factor Structure and Reliabilitymentioning
confidence: 97%